THE IMPORTANCE OF MEANING IN ARABIC TEXTBOOK TRANSLATION - Hanifah Hikmawati (Arabic Literature Department, 2021)
The translation process includes transferring the source language into the target language with the intention of knowing the meaning. When meaning is expressed to the reader, then all information, insight, and knowledge can also be understood. As in textbooks, knowledge conveyed through texts in it of course have references from foreign languages, including Arabic. Therefore, in this article there are several objectives; (1) becoming one of the references for writers and translators in understanding the importance of the translation process to find out the meaning of writing textbooks, (2) helping students and students learn to understand science through printed books. In particular, the discussion in this article is focused on understanding, strategies and the urgency of meaning in Arabic translation which is applied to writing lesson texts. This article uses a qualitative descriptive method. The data obtained are sourced from observations, findings, and literature reviews from various sources. The results of the analysis of this article are in the form of emphasizing the importance of the translation process as language transfer and messages from the source text which includes the source language into the target text which includes the target language. The translation process must refer to the understanding of both languages, and involve the sensitivity and feelings of the translator. This translation strengthens the position of language and cultural differences that are no longer a barrier in the development of science. Thus, by using a good and correct translation process, the meaning of textbooks can be fully grasped